Analisis Pengaruh Handover Terhadap Kinerja Video Streaming Menggunakan Protokol LTE - Ryan Eko Listyanto; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
LTE (Long Term Evolution) is a technology that dominates the cellular network developments for mobile nodes currently. LTE can carry out handovers to increase network capacity and support services to mobile nodes. On the other hand, at this time, video streaming is becoming a popular service with mobile nodes support capable of accessing high-quality video and support for LTE as a high-speed network of up to 150 Mbps. However, the handover mechanism on LTE can affect service quality due to channel shifting between eNodeB that is influenced by various things, for example, the number of nodes served, packets sent, or a drop in the signal that occurs on both eNodeB. This research is conducted a handover simulation with several scenarios using a micro cell. The simulation is carried out with four scenarios, namely node speed, node density, the distance of two eNodeB, and the size of packets sent. In the simulation, the nodes will move linearly between two eNodeB for 1000 seconds to get the results of end-to-end delay, jitter, packet loss, and throughput. From this test, it was found that nodes that were moving too slowly had suboptimal results. The higher network load on testing node density and packet size decreases service quality but it is still in good condition for video streaming. Meanwhile, the decrease in signal strength can improve service quality at some point.